(untitled) (Third Sector Social Economic Review, 2018)
It is aimed to grow the sector and to have a big share in the economy, with support applications in the fisheries sector. It is also aimed at protecting existing resources, ensuring traceability, preventing unregistered and unregistered production, enabling producers to compete with other countries in foreign market conditions, developing environmentally friendly production techniques and systems, increasing the quantity of water products, quality and domestic consumption. Supports made to fisheries sector in Turkey has provided great development. In this aspect, it will be useful to know the future areas and conditions of the investment and planning of the future development of the fisheries sector. With this work on support the implementation of the fisheries and aquaculture sector in our country is aimed to reveal the most current form. Also, İt is aimed to be resource reference for those who want to get information about supported fisheries product.